Relative abundance, activity pattern and habitat suitability of Great Argus (Argusianus argus grayi) in Sungai Wain Protected Forest, Balikpapan, East Kalimantan - Ramadhanti, Hanny; Perwitasari-Farajallah, Dyah; Mulyani, Yeni Aryati; Rianti, Puji (Bogor Agricultural University, Indonesia, 2025)
Great Argus (Argusianus argus) is a globally threatened species that is protected by law in Indonesia. This species is a habitat specialist that tends to be confined to primary forests and is susceptible to human disturbance and environmental change. Sungai Wain Protected Forest (SWPF) is an isolated lowland rainforest in Kalimantan. The rising deforestation rate has threatened species sustainability in recent decades, including the Great Argus in SWPF. This study aimed to systematically analyze camera trap data on the Great Argus's abundance, activity patterns, and habitat suitability prediction in SWPF. We used camera trap data from 2018-2022 at the SWPF. Great Argus's lowest relative abundance index was in 2020, and the highest was in 2022. Overall, the relative abundance index of the Great Argus was approximately 3.125 independent events per 100-day trap night. The activity pattern of the Great Argus started at dawn and then constantly decreased until dusk. The habitat suitability prediction for the Great Argus was mostly in primary forests. Distance to road and building were the variables that contributed the most to the results of habitat suitability modeling. Habitat loss and suitability are the determining factors for the sustainability of significant argus populations.